THE MODEL OF INFORMATION AND ANALYTICAL SUPPORT OF EDUCATIONAL RESEARCH BASED ON ELECTRONIC SYSTEMS OF OPEN ACCESS - Oleg M. Spirin; Anna V. Іatsyshyn; Svitlana M. Ivanova; Alla V. Kilchenko; Liliia A. Luparenko (Інформаційні технології і засоби навчання, 2017)
The article presents the experience of using electronic open access systems for information and analytical support of pedagogical research, which positively influences the quality of scientific research. A well-founded system of information and analytical support of pedagogical research based on electronic open access systems corresponds to the scientific and pedagogical needs for implementation: the publication, dissemination and use of information resources. The use of this system will improve the quality of scientific and pedagogical research conducted at the institutions of the National Academy of Educational Sciences of Ukraine, and will effectively implement their results in the scientific and educational sphere of Ukraine. The model of information and analytical support of scientific research is substantiated and developed. Specific features of the functioning of the prototype of an electronic scientific journal on the platform of open journal systems are determined. The stages of implementation of the prototype on the platform of open journal systems that can be used by scientific institutions and higher educational institutions for the publication of scientific professional journals and collections are described.